2017
DOI: 10.2106/jbjs.cc.17.00030
|View full text |Cite
|
Sign up to set email alerts
|

Brugada Syndrome Induced by an Interscalene Block

Abstract: Brugada syndrome is an abnormality of the cardiac conduction system that leads to cardiac arrhythmias. Several anesthetic agents trigger Brugada-like electrocardiographic abnormalities. To our knowledge, this is the first report of an interscalene block inducing Brugada syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Furthermore, it is known to act on EP1 subtype of prostaglandin E2 and reducing inflammation and hyperalgesia (74).It has been listed as a class IIa drug for patients with brugada with the studies having shown it to be pro arrhythmic for such patients (12). In our review we observed patients previously having masked brugada pattern showing a classical brugada pattern on ECG without any symptom after administration (21,45), however there were studies showing ventricular fibrillation (29) and cardiac arrest (40) in patients thus highlighting its potential risk.…”
Section: Bupivacainementioning
confidence: 85%
“…Furthermore, it is known to act on EP1 subtype of prostaglandin E2 and reducing inflammation and hyperalgesia (74).It has been listed as a class IIa drug for patients with brugada with the studies having shown it to be pro arrhythmic for such patients (12). In our review we observed patients previously having masked brugada pattern showing a classical brugada pattern on ECG without any symptom after administration (21,45), however there were studies showing ventricular fibrillation (29) and cardiac arrest (40) in patients thus highlighting its potential risk.…”
Section: Bupivacainementioning
confidence: 85%
“…23 , 24 However, an interscalene block using 30 mL of 0.5 % bupivacaine did result in a ventricular fibrillation arrest. 25 An axillary block has been successfully preformed using ropivacaine and coinciding empiric intralipid treatment. 26 An ilioinguinal block, sub-tenon’s block, peribulbar block, and intraoral injection for tooth extraction have all been unremarkable with no arrhythmias or EKG changes.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%